Congenital Arthrogryposis and Maternal Myasthenia - J Gordon Millichap (Pediatric Neurology Briefs)
An infant with arthrogryposis multiplex and other malformations born to a mother who presented with myasthenia gravis immediately following cesarean section is reported from the Depts Neonatology and Obstetrics, Hasharon Hospital, Petah-Tiqva, Tel Aviv Univ Med Sch, Israel.